Assédio moral em organizações militares: em busca de uma gestão de pessoas com subjetividade - Coelho, Marcos Fábio (2009)
This study aimed to identify the pratices of moral harassment in military institutions, as well as the repercussion on the welfare psychological and physical of civil and military employees. For such, it was necessary to perform the data-colleting through seven interviews comprehending employers of different sorts and hierarchical levels. The data were analyzed by method of contents for categories. During the research it was possible to detect that the naturalization of the power, clear-cut in the hierarchies, contribute to the pratices of moral harassment. In the relation between dominant and dominated, the speeches established shown that the disqualification of the person who suffers harassment reinforce much more that person who pratices harassment. The data has pointed to there is not preocupation about subjectivity of worker, but it has pointed to your productivity, what it unchained diverse conflicts in the interpersonal relations. Six categories were analyzed: formation, phases of the moral harassment , adaptation, naturalization of the power, disqualification, feelings and symptoms; of which it extracted sub-categories. Thus being, this study it is relevant to the field of administration with respect to the management and the quality of life in the work.